Between interpretation and morality: Anti-shippers in modern media fandom - Ciesielska, Dominika; Rutkowska, Maria (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
Shipping, as one of the most popular fan practices, is highly affective, and there are different meanings ascribed to it. Different interpretations of the source text made by fans and the different ships that are fashioned based on them create conflicts and divisions within the fandom. On the basis of this, the phenomenon of anti-shipping and shipwars has emerged. This article, focusing on media fandoms, aims to showcase this issue by presenting fandom discussions and arguments motivated by emotions around ships: from ship wars waged by shippers competing with each other, to anti-shippers driven by moral motives in the form of introducing the fandom purity wank issue and anti-shippers of celebrity pairings. By researching the field of fan studies and media studies, the authors aim to find the motivation and reasons for the sometimes extreme behavior of anti-shippers. The gool is to show the diversity of media fandoms and the importance of fans’ own interpretations of the source text and their ship of choice for the fans themselves.